PENGGUNAAN PERANGKAT MULTIMEDIA SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR - A’zizah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The use of multimedia devices in Islamic Religious Education at SMP Negeri 3 Simeulue Timur. In this study, it was found that the use of multimedia devices was not effective in improving student learning outcomes. Some of the obstacles that become obstacles include the need for more motivation from ICT teachers, students' lack of understanding and skills in using multimedia devices, and problems with school facilities. However, if these factors can be overcome, multimedia devices can still improve student learning outcomes in Islamic Religious Education subjects. Therefore, guidance and training are needed for teachers and students, as well as the improvement of school facilities so that multimedia devices can be more optimal. With the help of multimedia devices, it is hoped that students can learn in a more interactive and motivating manner, as well as assist teachers in presenting learning material more clearly and easily understood by students